Three essays on financial wellness in the workplace - Spann, Scott M. (Kansas State University, 2014)
This dissertation, consisting of three studies, explores the factors that influence the financial wellness of employees participating in a workplace financial education program. This dissertation also explores the influence that financial wellness has on the intention to engage in retirement planning activities and perceived retirement preparedness. Data for all three essays was obtained from a Financial Wellness Assessment instrument used in conjunction with a workplace financial education program provided by Financial Finesse (2013). The primary conceptual framework used to guide the three studies was Joo’s (2008) conceptual framework of financial wellness. The first essay examined factors that have been conceptualized as components of financial wellness—financial behaviors, perceived financial knowledge, and financial attitudes. Results showed that employees comfortable with their current level of non-mortgage debt and those with perceived financial knowledge had a greater sense of overall financial wellness. Core financial behaviors and advanced financial behaviors were also found to be associated with financial wellness with core financial behaviors having the biggest effect on financial wellness. Maintaining an emergency fund, having a handle on cash flow, paying credit card balances off in full each month, and paying bills on time were significantly related to greater financial wellness. Personal factors associated with a greater sense of financial wellness included household income, being under age 30, homeownership, being married, and not having children in the household. The second essay examined the influence of various subcomponents of financial wellness on retirement planning intention. Results indicated that retirement was the leading financial topic of interest of employees. Findings also demonstrated that desirable core financial management behaviors and a financial attitude of comfort regarding current non-mortgage debt increased the likelihood of employee intentions to engage in retirement planning activities. Specific financial behaviors associated with retirement planning intention included having a handle on cash flow, paying bills on time, and paying off credit card balances in full each month. Personal factors such as age and income also influenced retirement planning intention as older employees and those with greater household income were more likely to intend to plan for retirement. Having children in the household and non-Caucasian/White ethnicity decreased the likelihood of retirement planning intention. Finally, the third essay utilized Joo’s (2008) conceptual framework of financial wellness to explore factors that predict perceived retirement preparedness. Higher levels of financial satisfaction, perceived financial knowledge, and confidence in current asset allocation increased the likelihood employees demonstrated a sense of retirement preparedness. Core and advanced financial behaviors were also associated with perceived retirement preparedness. Younger employees and household income of $100,000 or more increased the likelihood of perceived retirement preparedness. Results of these three studies demonstrate that financial wellness has a significant influence on perceived retirement preparedness of employees engaged in information seeking activities as part of a workplace financial education program. Key components of financial wellness such as objective financial status, financial knowledge, financial attitudes, financial satisfaction, and financial behaviors were also found to be associated with the intention to engage in retirement planning activities. These findings are relevant to financial counselors, financial planners, financial educators, academicians, and employers dedicated to promoting increased financial wellness among employees.
Keywords: Financial behavior; Financial wellness; Financial well-being; Financial education; Retirement planning; Retirement preparedness; Business Education (0688); Economics, Finance (0508); Social Sciences Education (0534)